2008
DOI: 10.1308/003588408x301154
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Interhospital Transfer and Emergency MRI for Suspected Cauda Equina Syndrome: A 2-Year Retrospective Study

Abstract: INTRODUCTION The timing of surgery in cauda equina syndrome due to prolapsed intervertebral disc remains controversial. Assessment of these patients requires magnetic resonance imaging (MRI), which is of limited availability outside normal working hours in the UK. PATIENTS AND METHODS We reviewed radiological results in all patients undergoing emergency MRI within our unit for suspected cauda equina syndrome over a 2-year period, and all subjects undergoing emergency lumbar discectomy for cauda equina syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 6 publications
0
21
0
1
Order By: Relevance
“…Crocker et al [8,9,46], have addressed this issue along with that of the lack of out-of-hours MRI facilities in a large number of non-regional centres in UK which accept emergency admissions. In fact they found that of 82 patients referred with suspected CES and undergoing emergency MRI, the diagnosis was confirmed in 27 (33%), but only 5 patients required emergency surgery, 15 were on the next available daytime operation list and 6 had their surgery after more than 24 h. Clearly emergency MRI and surgery were probably of great importance for those five individuals who might otherwise have suffered disabling long term neurological compromise, but evidently these costly facilities were not essential for the other 77 patients.…”
Section: The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Crocker et al [8,9,46], have addressed this issue along with that of the lack of out-of-hours MRI facilities in a large number of non-regional centres in UK which accept emergency admissions. In fact they found that of 82 patients referred with suspected CES and undergoing emergency MRI, the diagnosis was confirmed in 27 (33%), but only 5 patients required emergency surgery, 15 were on the next available daytime operation list and 6 had their surgery after more than 24 h. Clearly emergency MRI and surgery were probably of great importance for those five individuals who might otherwise have suffered disabling long term neurological compromise, but evidently these costly facilities were not essential for the other 77 patients.…”
Section: The Literaturementioning
confidence: 99%
“…Thirdly, delays may occur in the hospital [39] with junior doctors and nurses not recognising the syndrome presented to them. Finally, the non-availability of out-of-hours MRI and specialist spinal surgical facilities may singly or collectively cause further delay [8] which may be critical to the eventual outcome, especially if there is evidence of progressing neurological deficit during this time. If any of those imperfections are found to be negligent then substantial damages may be awarded.…”
Section: Medico-legal Considerationsmentioning
confidence: 99%
“…2). Selection procedure and subsequent citation tracking resulted in 16 reports on 15 different studies that met all criteria [5,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. One study was reported in two publications [19,20].…”
Section: Characteristics Of Included Studies and Risk Of Biasmentioning
confidence: 99%
“…Owing to the high morbidity caused by CES, it is vital that patients suspected to have this condition are investigated and treated appropriately and efficiently 1 7 14 15. However, this report will explain the treatment of CES that goes far beyond the operating room, and requires true multidisciplinary team (MDT) input.…”
Section: Introductionmentioning
confidence: 99%
“…Patients may present late after not noticing subtle symptoms or signs, while doctors may also not be privy to these 1. These delays may be compounded by a lack of MRI out of hours in certain hospitals 7. This has resulted in many patients with CES having a delayed diagnosis, thus experiencing permanent dysfunction of their bowel, bladder or sexual function 1 4 8–11.…”
Section: Introductionmentioning
confidence: 99%